Sirtuin Evolution at the Dawn of Animal Life. (6th September 2022) - Gold, David A; Sinclair, David A
Abstract: Sirtuins are a family of proteins that protect against cellular injury and aging; understanding their evolution should reveal fundamental mechanisms governing longevity. "Early-branching" animals such as sea sponges and jellyfish have been understudied in previous analyses of sirtuin diversity. These organisms not only hold important positions at the base of the evolutionary tree, but also have unique aging dynamics that defy convention, such as quasi-immortality and high regenerative capacity. In this study, we survey the evolution of sirtuin proteins in animals, with a focus on the oldest living lineages. We describe previously unrecognized expansions of "Class IV" and "Class I" sirtuins around the origin of animals, raising the number of sirtuin families in the last common ancestor to at least nine. Most of these undescribed sirtuins have been lost in vertebrates and other bilaterian animals. Our work also clarifies the evolution of PNC1 and NAMPT enzymes that carry out the rate-limiting step in sirtuin-related NAD + biosynthesis. The genes for PNC1 and NAMPT enzymes were both present in the first animals, with the genes being lost a minimum of 11 and 13 times, respectively, over the course of animal evolution. We propose that species with these ancestral gene repertoires are ideal model organisms for studying the genetic regulation of animal longevity and will provide clues to increasing longevity in humans.